2023
DOI: 10.1111/cas.15692
|View full text |Cite
|
Sign up to set email alerts
|

HKDC1 upregulation promotes glycolysis and disease progression, and confers chemoresistance onto gastric cancer

Abstract: There is increasing evidence that hexokinase is involved in cell proliferation and migration. However, the function of the hexokinase domain containing protein‐1 (HKDC1) in gastric cancer (GC) remains unclear. Immunohistochemistry analysis and big data mining were used to evaluate the correlation between HKDC1 expression and clinical features in GC. In addition, the biological function and molecular mechanism of HKDC1 in GC were studied by in vitro and in vivo assays. Our study indicated that HKDC1 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The first recently found that HKDC1 can promote chemoresistance, proliferation and invasion, and epithelial-to-mesenchymal transition through induction of NF-κB. 51 The second study suggests HKDC1 may be pivotal for glycolysis and proliferation in AGS and MKN-45 GC cells. 52 Supporting a relevant role for HKDC1 in carcinogenesis, this gene has been found to promote lung, 53 breast, 54 and biliary 55 cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The first recently found that HKDC1 can promote chemoresistance, proliferation and invasion, and epithelial-to-mesenchymal transition through induction of NF-κB. 51 The second study suggests HKDC1 may be pivotal for glycolysis and proliferation in AGS and MKN-45 GC cells. 52 Supporting a relevant role for HKDC1 in carcinogenesis, this gene has been found to promote lung, 53 breast, 54 and biliary 55 cancers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, HKDC1 is found to promote glycolysis and disease progression in gastric cancer. 18 Besides, HKDC1 was proven to enhance glycolysis and accelerate endometrial cancer progression. 16 However, in liver cancer, it is reported that HKDC1 promoted liver cancer progression through its interaction with mitochondria instead of enhancing glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…As a hexokinase, HKDC1 has been reported to be upregulated and promoted glycolysis in certain cancers. For example, HKDC1 is found to promote glycolysis and disease progression in gastric cancer 18 . Besides, HKDC1 was proven to enhance glycolysis and accelerate endometrial cancer progression 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations